2014
DOI: 10.1007/s00056-014-0231-y
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of a self-adhering flowable composite when used for lingual retainer bonding

Abstract: When applied to bond lingual retainers to unetched enamel or with self-etching bonding agent accompanied by an additional acid etching, Vertise™ Flow resulted in a significant decrease in bond strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
4
11
1
4
Order By: Relevance
“…Our findings showed that both adhesive and mixed modes of failure characterized the fractures seen with Vertise Flow, which was consistent with other studies (Juloski et al, ; Veli et al, ). However, in groups used to test the adhesive associated with Premise Flowable composite, the most frequent fracture modes were cohesive and mixed.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed that both adhesive and mixed modes of failure characterized the fractures seen with Vertise Flow, which was consistent with other studies (Juloski et al, ; Veli et al, ). However, in groups used to test the adhesive associated with Premise Flowable composite, the most frequent fracture modes were cohesive and mixed.…”
Section: Discussionsupporting
confidence: 93%
“…TBLR has been developed specifically for bonding lingual retainers and is used extensively in clinical practices and recent experimental studies, commonly as the control adhesive [16,19,21,23]. TBXT is an orthodontic bonding adhesive resin used mostly for brackets but has been occasionally used for the construction of fixed retainers in the laboratory setting [5,22,23]. The rest of the three products were tested for comparison purposes.…”
Section: Discussionmentioning
confidence: 99%
“…ACC is a flowable composite, IPS-ED is a nanohybrid and ZNano a nanoparticle restorative composite. Although these materials have no indication for orthodontic bonding, restorative dental resin has been used in the past for the preparation of lingual retainers in a clinical or laboratory setting [2,23]. Recently, some flowable composites, originally created for restorative dentistry, have been used for the construction of fixed retainers [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only when measured immediately after application [28], but especially after aging [29,30], self-adhesive composites present significantly lower bond strengths than conventional composites that were applied with a bonding system in the etch-andrinse or self-etch technique. Chemical bonding of GPDM to the calcium present in hydroxyapatite has been positively demonstrated [31]. Unlike etch-and-rinse adhesives, self-adhesive composites are applied directly on the smear layer of dentin surface; etching and subsequent penetration of monomers into the demineralized dentin are carried out as a single step, which is achieved by including polymerizable acidic monomers into the formula [32].…”
Section: Discussionmentioning
confidence: 99%